Revisión Bibliográfica del uso de materiales innovadores en el diseño y construcción de puentes (2023)
The study is conducted using the Parsifal tool, which serves to carry out an assessment of scientific and technical documentation associated with innovative materials in the design, construction, and maintenance of bridges. The main objective is to identify trends and progress in the implementation of these materials throughout the life cycle of bridge structures. Articles from major academic sources were collected and analyzed, with a notable contribution from Scopus in the article selection process. The results indicate a noticeable increase in research on innovative materials from 2018, possibly driven by technological advances, demands for safer and more sustainable infrastructure, and public awareness. Findings are categorized into three areas: bridge design, construction, and maintenance, revealing the influence of materials such as Ultra HighStrength Concrete and Fiber-Reinforced Polymers. Furthermore, the characteristics and feasibility of these materials are evaluated, highlighting their durability, strength, and construction efficiency, as well as their environmental impact. Despite higher initial costs, it is evident that their availability and long-term advantages are quite extensive. The study also provides an insight into the possibilities and challenges faced in implementing innovative materials in bridge construction, supporting the improvement of safety and sustainability in road infrastructure.